Rapid Assessment of Agriculture Vulnerability to Drought using GIS - Bambang H. Trisasongko; Dyah R. Panuju; Harimurti; Adi F. Ramly; Heru Subroto (International Journal of Technology, 2016)
Food production, particularly rice, has been one of the major concerns in Indonesia. Primary threats to production include agricultural land conversion and climate change. In this paper, a GIS-based approach is presented to assess agricultural drought. This approach was developed using the water balance technique, which accounts for spatial population data. We found that agricultural fields in the Upper Bengawan Solo basin were fairly vulnerable to drought, mainly due to expanding Surakarta (Solo) city.